Effects of different concentration of both naphthaleneacetic acid and 6-benzylaminopurine in callus induction of capsicum frutescens / Nursuria Md. Setamam - Md.Setamam, Nursuria (Universiti Teknologi MARA Cawangan Pahang, 2019)
Capsicum frutescens var. bird's eye chili belongs to Solanaceae family is known to have economic properties due to its secondary metabolites such as capsaicin that can be used to treat various diseases. In tissue culture, this plant is often been associated with recalcitrant which inability to regenerate in in -vitro environment. Therefore in order to overcome this challenge, callus culture becomes one of the important approaches to gain result in many tissue culture studies. Callus induction of C. frutescens can provide many tremendous benefits such as somatic embryogenesis and genetic engineering. In this study, the effect of naphthaleneacetic acid (NAA) and 6- benzylaminopurine (BAP) in different concentration becomes subject of interest as to obtain optimum result in term of growth formation, earliest initiation and morphology of callus that may become the key factor for successful future studies that related with C. frutescens. The foliar explants of C. frutescens were chosen as explant sample and further been sterilized by using 15% NaOCI and ethanol 70%. The explants were then been cultured in MS media with seven different treatments contained NAA and BAP (0.0 + 2.5, 2.5+0.0, 2.5+2.5, 2.5+5.0, 5.0+2.5, 2.5+10.0, and 10.0+2.5 mg/L) for one month. The result had shown that, treatments with concentration of NAA (2.5 mg/L) and BAP (5.0 mg/L) had gained optimum level for earliest callus initiation in day 5 with highest callus growth. The result also has the best callus morphology which was pure white, friable and soft texture which suitable to be used in future studies.